1998
DOI: 10.2214/ajr.171.4.9762991
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous hepatic infarction therapy for hepatocellular carcinoma.

Abstract: OBJECTIVE. We percutaneouslyinjected ethanol into small vesselsafferent to tumor nodules to induce hepatic infarction in areas of tumor caused by hepatocellular carcinoma. CONCLUSION. Percutaneous hepaticinfarctiontherapyholdspromiseasa new method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Previously, Imamura et al [9] reported the possibility of treating hepatic infarction by injecting ethanol into the hepatic artery for the treatment of HCC. In recent years, there have been doubts about whether hepatic infarction is desirable to maintain functional hepatic reserve, but an intra-arterial ethanol injection is very effective for hemostasis when HCC ruptures.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Imamura et al [9] reported the possibility of treating hepatic infarction by injecting ethanol into the hepatic artery for the treatment of HCC. In recent years, there have been doubts about whether hepatic infarction is desirable to maintain functional hepatic reserve, but an intra-arterial ethanol injection is very effective for hemostasis when HCC ruptures.…”
Section: Discussionmentioning
confidence: 99%